A framework for understanding culture and its relationship to information behaviour: Taiwanese aborigines' information behaviour - Nei-Ching Yeh (Information Research: An International Electronic Journal)
Introduction. This article proposes a model of culture and its relationship to information behaviour based on two empirical studies of Taiwanese aborigines' information behaviour. Method. The research approach is ethnographic and the material was collected through observations, conversations, questionnaires, interviews and relevant documents. In 2003-2004, the author lived with two Taiwan aboriginal tribes, the Yami tribe and the Tsau tribe and conducted forty-two theme-based interviews. Analysis. Data were analysed with the help of software for qualitative analysis (NVivo), where all sentences from both interviews and field notes were coded. The conceptual framework used is the sociology of knowledge. Results. The model of culture and its relationship to information behaviour can show us how to think about the relationship between culture and human information behaviour. This model also identifies elements of the model, which are habitus, tradition and prejudice and suggests how we can apply the concepts of information fullness and emptiness to view the relationship between culture and human information behaviour. Conclusion. . Theoretically, this research puts forward a new model of information behaviour and focuses on the role and the importance of culture when thinking about and studying human information behaviour. Methodologically, this study demonstrates how an ethnographic research method can contribute to exploring the influence that culture has on human life and the details of the human life world and information behaviour.